Relationship between serum IgG level, fractional exhaled nitric oxide and microbial contamination in metalworking fluids among machinists in Nilai, Negeri Sembilan, Malaysia - Hashim, Nuurl Maizura (2016)
Introduction: Metalworking fluids (MWFs) are commonly used in machining industry during metal working process such as cutting, turning, milling, drilling and grinding. Water based metalworking fluids (MWFs) are commonly used in machining industries and are excellent media for microorganism growth. Machining’s workers are most exposed to the contaminant of metalworking. Problem Statement: Machining industry is one of the industries in Malaysia that are rapidly growth. Soluble metalworking fluids (MWFs) are commonly used by machining industry. These fluids represent a high potential for health risk due to high water content present in the emulsion which is excellent for micro-organism growth. Respiratory problem and skin problem may be implicated by the microbial contaminants exposure of metalworking fluids (MWFs). Upper airway inflammation was a common problem among machinists and it is reported that, about 39% of the workers exposed to MWFs had airway symptoms. MWFs exposure containing a mixture of reactive and pro-inflammatory agents may induce a toxic response in the upper cell-linin, resulting in decreased formation of normally expressed immune defence protein. Objective: To study the relationships between serum IgG levels and airway inflammation with the microbial exposure among MWFs workers. Methodology: This cross sectional study was carried out on 138 machining workers exposed to MWF. Background, working, health and resedential information of respodents were collected by a set of questionaire adapted from American Thoracic Society (ATS-DLD-78). Two ml blood were drawn from the cubital to be tested for the level of total and specific IgG antibody in blood. The workers’ FeNO were measured using NIOX-MINO instrumentation. The microbial assessments were carried out on the MWF bulk samples and the aerosol in the work environment. DUO SAS SUPER 360TM sampler was used to sample the bacteria and fungi in the air. The data were analysed using the SPSS Version 22.0. Result and Discussion: This study found that, the mean value for the environmental bacteria and fungal in all work sections were 285.83cfu/m3 and 231.2cfu/m3 respectively. Whereas, the means for microbial contamination in bulk samples were 37916.7 cfu/ml3 (bacteria) and 38833.3 cfu/ml3 (fungal) respectively. The mean of the IgG in all work sections was 13.79 g/litre. The environmental bacteria levels has a significant correlation with the total IgG antibodies levels (p=0.003). There were also a significant relationship between BMI (p=0.044), work duration (p=0.014), smoking (p=0.014) and environmental contaminants (0.049)with the total of IgG.levels Findings also showed significantly difference in the FeNO levels of workers from various work sections (p=0.01). From the multivariate statistics, there were also significant relationships between the high FeNO with their closeness between machines (p=0.03), higher number of machines (p=0.02), high environmental bacteria colonies (p=0.04), longer employment years (p=<0.001) and frequent reporting of respiratory symptom such as cough (p=0.03). Conclusion: There were significant correlations between the total IgG antibodies levels with the microbial contaminants of metalworking fluids in metal working process. Besides, there were also significant relationships between work duration, smoking, BMI and environmental contaminants with the total IgG.levels. Risk factors from the workplace such as the number of machines, closeness between machines and high environmental bacteria colonies and longer employment years had significant relationships with the airway inflammation (FeNO). Exposure to MWF also resulted in significantly frequent cough symptom.